Prevensi Fatwa MUI tentang Pernikahan di Bawah Tangan Perspektif Maqashid al-Syari'ah - Ulya, Zakiyah; Khair, Umul (KIPS Institute Bukittinggi, 2025)
Unregistered marriage (nikah siri) remains a prevalent marital practice in Indonesia despite its lack of recognition under state law. This practice gives rise to various legal and social problems, particularly affecting women and children, including uncertainty regarding legal status, lineage, and the protection of rights to maintenance and inheritance. These conditions prompted the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) to issue Fatwa No. 10 of 2008 on Unregistered Marriage. This study aims to analyze the fatwa from the perspective of maqa?id al-sharia. The research employs a normative legal method with a qualitative approach through library research, examining the MUI fatwa, statutory regulations, classical fiqh literature, and relevant scholarly journal articles. The findings indicate that MUI recognizes the validity of unregistered marriage from a fiqh perspective insofar as the essential pillars and conditions of marriage are fulfilled; however, it deems such marriages unlawful when they result in harm (ma?arrat) and recommends official marriage registration as a preventive measure. Nevertheless, the fatwa is considered ambiguous because it fails to provide clear criteria for determining harm. From the perspective of maqasid al-sharia, the practice of nikah siri generally contradicts the objectives of Islamic law, particularly in safeguarding religion, life, intellect, lineage, and property. Therefore, official marriage registration constitutes an essential instrument for realizing public welfare, legal certainty and the protection of family rights within Indonesia’s Islamic legal system.